Rancangan Alat Bantu Pembelajaran Salat untuk Siswa SLB Bagian B Tunarungu Berbasis Multimedia - Vany Varha Vauzia; Diana Effendi (Universitas Islam Sumatera Utara, 2020)
Currently SLB Negeri Cicendo students still need special teaching so that information and material are conveyed properly. The media used for teaching and learning activities of the prayer movement is also still conventional in nature, and therefore the design of Interactive Multimedia Applications for Prayer Learning which contains the material of prayer, prayer movement and, evaluation of material. Data collection research methods conducted were observation, interviews and also documents. In addition, the approach method used in this study uses an object-oriented approach with UML tools, namely use cases, scenario diagrams and activity diagrams, while the method of development is carried out with a prototype model. The purpose of this application was made to make it easy for teachers to be able to convey material with interesting aids, and also make it easy for deaf students to receive material and reading while measuring the ability of deaf students.